Bureaucratic Implications of SKB No. 3 of 2008 on Politics Identity of the Ahmadiyya Congregation - Alexandro Arthur Constantine; Dewi Yuliantika; Laras Nanda Marjuningtyas; Salsabila Widyadhari; Muhamad Revan Athallah (International Journal of Islamic Khazanah, 2022)
The emergence of the rejection of the construction of the Indonesian Ahmadiyya Congregation Mosque (JAI) in Garut Regency, West Java, resulted in the sealing of the mosque on the publication of Circular Letter No. 3 of 2008. This gave rise to the phenomenon of the power of the central and regional governments in limiting the continuity of the religion of the JAI group. The focus of this research in this article is to see Marxist thinking related to bureaucracy where the emergence of SKB No. 3 of 2008 bureaucracy can influence identity politics. This study uses a qualitative approach with descriptive methods and data collection techniques for library research and documentation. In freedom of religion, the bureaucracy is used as a tool of power to limit certain social groups. The occurrence of community resistance to the JAI group in fighting for their religious freedom.